Southwest monsoon-driven changes in the phytoplankton community structure in the central Arabian Sea (2017–2018): After two decades of JGOFS. (September 2021) - Chowdhury, Mintu; Biswas, Haimanti; Mitra, Aditi; Silori, Saumya; Sharma, Diksha; Bandyopadhyay, Debasmita; Shaik, Aziz Ur Rahman; Fernandes, Veronica; Narvekar, Jayu
Graphical abstract: Highlights: Phytoplankton community structure was linked to surface wind forcing. Nutrients (bottom-up) and grazing (top-down) shape the phytoplankton community. While comparing with the JGOFS reports, no considerable community shift was noticed. Monsoon wind variability may directly influence large diatom abundance and export flux. Abstract: The Arabian Sea, a land-locked low latitude high productive oceanic province, is characterized by strong seasonality due to the reversal of monsoon winds. "Open ocean upwelling" occurs during the southwest monsoon (SWM) in the northern part of the Findlater Jet, (a low-level atmospheric jet that forms in the Arabian Sea), and consequently, the southern part experiences downwelling. Moreover, the hydrography of this region can be further modulated by coupled ocean-atmospheric events such as ENSO and IOD which eventually lead to changes in biological production. After two decades of joint global ocean flux studies (JGOFS), this is the first report on the phytoplankton community from the central Arabian Sea during the SWM. We tried to interlink the north-south gradient in hydrography as well as the physicochemical features with the phytoplankton community structure (within 60 m) along 64° E (11–21° N) during two consecutive SWM cruises (August 2017 and 2018). The variability in surface wind forcing directly influenced the nutrient stoichiometry and phytoplankton dynamics, through the changes in open ocean upwelling and mixing. Significant spatial and inter-annual variability in phytoplankton abundance, diversity, ratios of diatom: dinoflagellate and centric: pennate diatoms were noticed and were closely coupled with the nutrient availability (bottom-up control). Relatively low phytoplankton cell density in 2017 was coupled with high zooplankton biomass (top-down control). During 2018, higher dissolved silicate (DSi) supply due to stronger open-ocean upwelling along with the advection of upwelled water from the Somali coast likely promoted larger diatoms capable of escaping grazing and have led to higher export production. The large centric diatoms occupied the upwelled regions (21–20° N) (e. g. Rhizosolenia imbricata, R. hebetata and Coscinodiscus radiatus ) whereas, small pennate diatoms ( Pseudo-nitzschia spp., Navicula spp. Nitzschia spp.) and dinoflagellates ( Gymnodinium spp.) were pronounced in the south (11–15° N). And while comparing the trends with the JGOFS reports, no considerable community shift was noticed. However, in the context of ongoing climate change, the rapid warming of the Arabian Sea may potentially influence the hydrography and biogeochemistry of this region and thus may impact phytoplankton community structure, trophic transfer, and organic carbon export flux.